2014
DOI: 10.1038/ncomms6709
|View full text |Cite
|
Sign up to set email alerts
|

A trident dithienylethene-perylenemonoimide dyad with super fluorescence switching speed and ratio

Abstract: Photoswitchable fluorescent diarylethenes are promising in molecular optical memory and photonic devices. However, the performance of current diarylethenes is far from satisfactory because of the scarcity of high-speed switching capability and large fluorescence on-off ratio. Here we report a trident perylenemonoimide dyad modified by triple dithienylethenes whose photochromic fluorescence quenching ratio at the photostationary state exceeds 10,000 and the fluorescence quenching efficiency is close to 100% wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 34 publications
(39 reference statements)
1
91
0
1
Order By: Relevance
“…Vis. [29][30][31][32][33][34][35][36][37] . Some of these derivatives can achieve reversible fluorescence photoswitching even at the singlemolecule level [31][32][33] .…”
Section: Molecular Systems Consisting Of Fluorescent and Photochromicmentioning
confidence: 99%
“…Vis. [29][30][31][32][33][34][35][36][37] . Some of these derivatives can achieve reversible fluorescence photoswitching even at the singlemolecule level [31][32][33] .…”
Section: Molecular Systems Consisting Of Fluorescent and Photochromicmentioning
confidence: 99%
“…[20][21][22] Despite their wide variability,t he lack of derivatives in which the closed form has astrong fluorescence in the visible range has prevented their direct application in super-resolution imaging. Strategies to covalently link diarylethene switches with suitable fluorophores and to utilize the energy [23] or electron transfer [24] of the resulting multichromophoric systems have been successful, but require extended syntheses and result in rather large probes.L abeling structures with such extended probes can significantly alter the structures to be visualized. [23,25] As an alternative,s uitable modification of the diarylethene photoswitch itself could give direct access to the envisioned properties.Uno et al [26] und Gillanders et al [27] have reported that the closed form of photochromic diarylethene derivatives bearing sulfone groups can fluoresce,w hich inspired our research.…”
mentioning
confidence: 99%
“…The results indicated that the reversibly photoswitchable fluorescence property of PFPNs can be instantly used to fabricate photorewritable fluorescence patterning under the help of photomask. 18 MTT Assay and Confocal Imaging of PFPNs in Living Cells. The cytotoxicity of PFPNs (NP-N3) was estimated via MTT assay by using A549 cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%